Why they did it?: sex differences in the impact of mental health and substance use on motivations for offending - Craig, Jessica M. (Crime & delinquency, 2018)
This study examined how mental health issues and substance use relate to motivations for offending among a large sample of adjudicated youth who completed a community-based placement in a large southeastern state (n = 18,749). The extent to which these relationships differed by sex was also considered. Multinomial logistic regression models revealed that although both mental health issues and substance use were related to a variety of reasons for offending, these relationships differed and did not appear to influence one another. In addition, findings revealed that mental health issues and substance use have differential effects on reasons for offending across sex. Treatment implications are highlighted along with suggestions for future research.